Visual exploration dynamics are low-dimensional and driven by intrinsic factors - Andrea Zangrossi (Nature Portfolio, 2021)
Andrea Zangrossi et al. analyze individual variability in eye movements when healthy participants view images of natural scenes. Their results suggest that eye movement patterns can be summarized by three principle components, and depend more on subjects’ intrinsic characteristics than the visual contents of the scene.